The Role of Privacy Awareness in Preventing Sexual Abuse: A Study on Primary School Students in Türkiye - Avci, Alperen (Wiley, 2026)
Purpose This study aimed to examine the relationship between primary school students' levels of privacy awareness and their knowledge of child sexual abuse, with particular attention to demographic and contextual factors including gender, socioeconomic status, and academic achievement. Methods A descriptive correlational research design was employed. The sample consisted of primary school students enrolled in public schools in T & uuml;rkiye during the 2023-2024 academic year. Data were collected using validated measures of privacy awareness and child sexual abuse knowledge. Descriptive statistics, independent samples t-tests, one-way ANOVA, Pearson correlation analysis, and multiple linear regression analysis were conducted to analyse the data. Findings The findings indicated that female students and older primary school students demonstrated significantly higher levels of both privacy awareness and knowledge of child sexual abuse. Students from higher socioeconomic backgrounds and those with higher academic achievement also showed greater awareness and knowledge. Overall, privacy awareness and sexual abuse knowledge were found to be at a moderate level but were strongly and positively correlated (r = 0.807, p < 0.01). Regression analysis further revealed that privacy awareness was a significant predictor of children's knowledge of sexual abuse (beta = 0.819, p < 0.01). Conclusion The results highlight the critical role of privacy awareness in enhancing children's protective knowledge against sexual abuse. Integrating systematic privacy education into primary school curricula may serve as an effective preventive strategy to strengthen children's self-protection skills and overall wellbeing.
Keywords: Primary School; Privacy Awareness; Sexual Abuse; Students